The Effect of Service Quality, Website Quality, Institutional Image Towards Public Satisfaction In The Cikini General Law Administration Office, Jakarta (KEMENKUMHAM) - Muhamad Ruskamto; Muhammad Anhar; Meita Pragiwani (BPJP - STEI, 2020)
This study aims to determine how the influence of service quality, website quality and agency image on public satisfaction in the General Law Administration (KEMENKUMHAM). This research method is a quantitative method using primary data and secondary data. The number of samples in this study were as many as 100 visitors. Data processing in this study used the SPSS version 23 analysis tool, and analyzed using multiple linear regression analysis. The analysis used in this study includes validity test, reliability test, coefficient of determination, multiple linear regression, and t test. The results showed that, (1) service quality has a significant effect on community satisfaction, (2) website quality has an effect on community satisfaction, (3) agency image has a significant effect on community satisfaction.